Preliminary research : Survei Penggunaan E-Modul Berbasis STEM (Sicence, Technology, Engineering and Mathematics) Pada Mata Pelajaran Biologi Kelas XI SMAN 5 Pekanbaru - Sari Nainggolan, Natalia; Suryanti; Hidayati, Nurkhairo (Jurnal Biogenerasi, 2024)
This research is motivated by the low use of electronic teaching materials, so that students are less active in the learning process and students have difficulty understanding the concept of biology subjects. The purpose of this study is to determine the use of e-modules as STEM-based teaching materials in biology subjects. This study uses a quantitative descriptive method using research instruments, namely observation sheets, interviews and questionnaires. The results of this study show that students' needs for the use of STEM-based e-models (Scince, Technology, Engineering and Mathematics) in biology subjects in grade XI of SMAN 5 Pekanbaru based on the results of observations, interviews and filling out questionnaires show that STEM-based e-models are needed by students, so it can be concluded that this is based on students' habits and needs when learning using technology such as smartphones, laptops, computers, or technology-based media that can access the e-module